Cyberformance and Children’s Theatre: a Contextual Examination of the Janelle and Joella Paradigm - Gana, Emmanuel Tsadu (The Journal of Society and Media, 2024)
This article identifies cyberspace as an alternate theatre environment for audiences to see performances.  There is no doubt that the internet has had a tremendous influence on human society; the interconnectedness and easy access to information and resources which it enables is a testament to this. Theatre artists have recently tapped into cyberspace to create content for an expanding online audience. This article explores how performance can enhance children's theatre in this digital space. It examines the concept of children’s theatre and defines children-centered online content as performance. The article broadens the definition of "liveness" in cyberformance to include not just live events but also pre-recorded content that engages viewers continuously. It analyzes three videos from Janelle and Joella, two sisters addressing children's issues online. This content is positioned within the framework of children-for-adult children’s theatre and identified as cyberformance. It highlights the videos' themes and presentation styles as exemplary of children’s theatre. Also, the attributes of performance, which are interconnectedness, liveness, and engagement, were established within the Janelle and Joella children’s theatre paradigm. The article concludes on the note that cyberformance offers a veritable platform for the continuous exploration of theatre.